Cutaneous manifestations of anti‐synthetase syndrome: Case series and literature review - Airiss R. Chan; Mohamed Osman; Elaine Yacyshyn; Robert Gniadecki (Wiley, 2024)
Abstract Background Anti‐synthetase syndrome (ASyS) is a rare inflammatory myopathy associated with anti‐aminoacyl transfer RNA synthetase antibodies, and is characterized by a triad of interstitial lung disease, arthritis, and myopathy. ASyS has been considered to represent a subtype of dermatomyositis (DM), however it is not clear whether cutaneous findings overlap in both diseases. Objectives We aimed to characterize mucocutaneous features which should raise suspicion of ASyS and prompt early diagnostic testing. Methods We reviewed 28 cases of ASyS in our institution, and retrieved data from 43 articles reporting clinical features of ASyS in the literature. Results Dermatologic manifestations of ASyS can be categorized as: specific cutaneous signs strongly associated with ASyS ('Mechanic's hands', 'Hiker's feet'); mucocutaneous signs overlapping with other collagenoses; nailfold changes (resembling those of DM and systemic sclerosis); and mucocutaneous signs of undetermined significance. Only 20% had pathognomonic DM signs. Conclusions Dermatologic manifestations of ASyS are heterogeneous and do not always reproduce the pattern seen in DM. Presence of palmar hyperkeratosis ('Mechanic's hands'), cuticular overgrowth, skin ulcerations and nailfold capillary changes should prompt further diagnostic workup of ASyS. Limitations of our study include inconsistent reporting of dermatologic findings within our series between virtual and in‐person visits. Not all patients were seen in dermatology consultation.